ULTRASTRUCTURE OF SALIVARY GLAND OF THIRD INSTAR LARVAE OF CHRYSOMYA MEGACEPHALA (DIPTERA) - NANCY TAHA MOHAMED, PHD (International Journal of Pharma and Bio Sciences, 2015)
The present study revealed the basic structure of salivary gland of third instar larvae of Chrysomya megacephala in order to clarify the source of proteolytic enzymes in the excretory/secretory products of this maggot. The salivary gland of third instar larvae of Chrysomya megacephala possess very well-developed cuticle, numerous rough endoplasmic reticulum with different shapes. Secretory products were observed beneath the cuticle. A large nucleus was observed nearly in the middle of the cell. Very well-developed musculature was seen throughout the cell. Numerous tracheae, mitochondria and other organelles were present throughout the cell. Thin basement membrane was observed with well-developed basal labyrinth that encloses numerous mitochondria. The structure of salivary gland cell of third instars larvae of Chrysomya megacephala indicate that salivary gland is responsible for a great part on the production of most of enzymes in the excretory/secretory products of this maggot.